GALA, a Database for Genomic Sequence Alignments and Annotations - Giardine, Belinda; Elnitski, Laura; Riemer, Cathy; Makalowska, Izabela; Schwartz, Scott; Miller, Webb; Hardison, Ross C. (Genome Research, 2003)
We have developed a relational database to contain whole genome sequence alignments between human and mouse with extensive annotations of the human sequence. Complex queries are supported on recorded features, both directly and on proximity among them. Searches can reveal a wide variety of relationships, such as finding all genes expressed in a designated tissue that have a highly conserved noncoding sequence 5′ to the start site. Other examples are finding single nucleotide polymorphisms that occur in conserved noncoding regions upstream of genes and identifying CpG islands that overlap the 5′ ends of divergently transcribed genes. The database is available online athttp://globin.cse.psu.edu/ and http://bio.cse.psu.edu/.